Trailing Harry Potter into Romanian - Ruxandra Drăgan (Linguaculture, 2021)
Characteristic of English and other Germanic languages, Goal of Motion constructions represent a challenge for any translator rendering them into a Romance language. This is because to express the motion of an entity to/towards a Goal in a particular manner, English typically combines a manner-of-motion verb or a verb of sound emission with a dynamic preposition like into in He ran into the park. However, the combination is not generally available in Romanian and other Romance languages, since they not only lack dynamic prepositions, but also have far fewer manner-of-motion verbs. Consequently, to render Goal of Motion into Romanian with as little loss as possible, a translator will have to resort to various translation techniques to compensate not only for the lack of dynamic prepositions in this language, but also for its far poorer class of manner-of-motion verbs. This paper proposes several strategies for the translation of Goal of Motion constructions into Romanian and shows that they depend on the lexical and syntactic resources available in this language. An analysis of the techniques employed in a selected sample from two Romanian translations of the Harry Potter series indicates that the translators' strategies generally mirror Talmy's (1985, 2000) typological classification of Germanic and Romance languages into satellite-framed and verb-framed languages, respectively.